Archery equipment shop in virtual reality environment (X-10 shop in VR) - Yousef A. Baker, El-Ebiary; Julaily Aida, Jusoh; Syarilla Iryani, A. Saany (2020)
VR technology has begun entering the repertoir of tools used by all parties. Today, sports goods business uses VR for visualization and sales. For example, VR is used as a promotional tool in selling goods to consumers and providing up-to-date information on the right prices and archery items. Very important, VR can help customers communicate better about the proposed plateform. Therefore, the proposed application for the X-10 Store in Virtual Reality is recommended. The X-10 Shop is a shop to provide information and pricing for beginner users on archery tools and they can also learn about archery equipment before buying it. The main objective of this research is to develop applications, to test the use of this application. This app is a platform for users to create users who want to buy archery tools and easy tools to view information and prices of archery equipment without having to go to the store and waste time to get there. This involves the use of Unity application development software to generate X-10 Shop in Realita Maya.